(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Rhodium(III) interacts with acridine yellow in hydrochloric acid solutions. The formed ion associate could be extracted by the dychlorethan–carbon tetrachloride (2.5+2.5) binary mixture, maximal extinction is observed at the value of wavelength 460 nm. Optimal acidity of aquans solutions is pH 2.0 by HCl. The optimal quantity of dye is 1.0–2.0 mL of 0,05% solutions. The coefficient of extraction is 92.6%. The range of determined concentration is 0.73–14.63 mcg of Rh(III) in 10 mL of aqueous phase. The value of seeming coefficient of acridine yellow tetrachlorrhodiate (III) ionic associates organic extracts molar extinction ε = 3.5·104 L·mol-1·cm-1. The molar ratio beetwin acridine cation and tetrachlorrhodiate (III) is 1:1.